Comparison of Absorbable versus Non Absorbable Tackers for Fixation of Mesh in Laparoscopic Midline Anterior Abdominal Wall Hernia Repair: A Randomised Clinical Study - Dhruv Gupta (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Tackers are divided in two broad categories namely, absorbable and non absorbable. Absorbable tackers are believed to achieve sufficient tensile strength compared to conventional non absorbable tackers. It is a matter of debate that which type of tacker has an upper hand over the other especially in terms of postoperative pain and recurrences even after few years of clinical experience with these tackers and available clinical studies. Aim: To compare various aspects of absorbable versus non absorbable tackers for fixation of mesh in Laparoscopic Midline Anterior Abdominal Wall Hernia Repair for short period of follow-up. Materials and Methods: In this prospective randomised clinical study from November 2016 till March 2018 at Atal Bihari Vajpayee Institute of Medical Sciences (ABVIMS) and Dr. Ram Manohar Lohia (RML) Hospital, New Delhi, India. Total of 80 patients of age ≥18 years with midline anterior abdominal wall hernia were included and randomised into two groups 40 patients each i.e. group 1 absorbable tackers and group 2 non absorbable tackers. Outcomes evaluated were postoperative pain, seroma formation, paralytic ileus, early recurrence (3 months follow-up) and duration of hospital stay.The data acquired was analysed using Statistical Package for Social Sciences (SPSS) version 22.0. Comparison of ordinal paired data was done using Wilcoxon signed rank sum test. The nominal categorical data was compared using Chisquare or Fisher’s-exact test as appropriate. A p-value of <0.05 was considered statistically significant. Results: Out of 80 patients included in this study with a range of 21 to 60 years, the median age was 30 years. There was no statistically significant association noted in terms of postoperative pain (p-value >0.05), seroma formation (p-value=1), paralytic ileus (p-value >0.05), length of hospital stay (p-value=0.801) and early recurrence (3 months). Conclusion: This study has shown that both non absorbable and absorbable tackers are associated with minimal postoperative complications and have similar postoperative morbidity. Both absorbable and non absorbable tackers are comparable for fixation of mesh in laparoscopic midline anterior abdominal wall hernia with respect to the above mentioned outcomes.